2014
DOI: 10.1097/jcp.0b013e3182a6082a
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization Resource Utilization and Costs Among Medicaid Insured Patients With Schizophrenia With Different Treatment Durations of Long-Acting Injectable Antipsychotic Therapy

Abstract: This study evaluated the impact of using long-acting injectable (LAI) antipsychotics for a longer treatment duration versus a short duration on health care resource utilization among Medicaid-insured schizophrenia patients. Schizophrenia patients 13 years or older initiating LAI antipsychotics were identified from the Truven Health Analytics MarketScan Research Medicaid database between July 1, 2005, and June 30, 2010. The study population was grouped into 2 study cohorts (longer-usage-duration cohort: ≥ 180 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Similarly, a study in a home health care setting in Taiwan showed a significantly lower risk for psychiatric rehospitalization in patients receiving LAI antipsychotics than those treated with oral medication [ 25 ]. In addition, a United States Medicaid database study reported that use of LAI medications is associated with a longer time to the first hospitalization for any cause and for schizophrenia; moreover, the authors also reported that a longer use duration of LAI antipsychotics (at least 6 months relative to those treated for shorter durations) is associated with a decreased number of hospitalizations, decreased hospital length of stay, and reduced hospital payment—thus using fewer hospital resources [ 26 ]. Findings from randomized clinical trials of olanzapine LAI have also produced similar results indicating favorable changes in hospitalization [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study in a home health care setting in Taiwan showed a significantly lower risk for psychiatric rehospitalization in patients receiving LAI antipsychotics than those treated with oral medication [ 25 ]. In addition, a United States Medicaid database study reported that use of LAI medications is associated with a longer time to the first hospitalization for any cause and for schizophrenia; moreover, the authors also reported that a longer use duration of LAI antipsychotics (at least 6 months relative to those treated for shorter durations) is associated with a decreased number of hospitalizations, decreased hospital length of stay, and reduced hospital payment—thus using fewer hospital resources [ 26 ]. Findings from randomized clinical trials of olanzapine LAI have also produced similar results indicating favorable changes in hospitalization [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…LAIs have been associated with both reduced hospitalization rates and care costs [17-19]. Clinical guidelines on LAI usage have been published, recommending that LAIs should not only be used to address nonadherence but also if patients have a basic preference for this formulation––for convenience or any other reason [20-22].…”
Section: Introductionmentioning
confidence: 99%
“…During the 12-month follow-up period, patients treated with LAI compared to oral antipsychotics had significantly lower average inpatient costs, higher average pharmacy costs, and similar total health care costs. 111 A recent Medicaid health care utilization study 112 in the United States compared health care utilization and treatment costs for hospitalized patients with schizophrenia who had been on short-duration LAI treatment (defined as 30-79 days; n = 2,856) versus longer-term LAI treatment (≥ 180 days; n = 2,838). The longer-term LAI patients had significantly lower levels of some health care utilization measures, including mean number of hospitalizations and mean length of hospital stay.…”
Section: Effect Of Lais On Adherence and Costsmentioning
confidence: 99%